(untitled) (African Journal of Biomedical Research, 2023)
Problem-based learning (PBL) method has been thoroughly and scientifically explored in a variety of fields but its viability for fostering preparation for self-directed learning readiness (SDLR) in a research method course has not yet been investigated. This study was aimed at evaluating the effect of PBL on SDLR among Nigerian nursing students who registered for a research methodology course. In this quasi-experimental study, a total of sixty-four 400-level nursing undergraduates were recruited from two government-owned universities in Southeastern Nigeria and randomly grouped into two: experimental and control groups who were exposed to PBL and traditional teaching methods (TTM) respectively from April through July 2021. Data was collected using a validated self-directed learning readiness scale (SDLRS) which was administered before and after the intervention while demographic information was obtained using a structured questionnaire. An SDLRS mean score of ≥ 3.75 implied a high SDLR. In the pre-test, SDLR gave an overall score of 3.99±0.39 and 3.87±0.44 for TTM and PBL respectively while the post-test gave an overall score of 3.84 ± 0.77 for TTM and 3.89 ± 0.84 for PBL. There was a statistically significant difference in the mean scores of pre-tests and post-tests (p=0.019). The PBL had a positive effect on the SDLR of Nigerian nursing undergraduates